2015
DOI: 10.1186/s12863-015-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuber shape and eye depth variation in a diploid family of Andean potatoes

Abstract: BackgroundTuber appearance is highly variable in the Andean cultivated potato germplasm. The diploid backcross mapping population ‘DMDD’ derived from the recently sequenced genome ‘DM’ represents a sample of the allelic variation for tuber shape and eye depth present in the Andean landraces. Here we evaluate the utility of morphological descriptors for tuber shape for identification of genetic loci responsible for the shape and eye depth variation.ResultsSubjective morphological descriptors and objective tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Bonierbale et al ( 1993 ) reported QTL on chromosomes 2, 4, and 7 for TTY, TS, and ATW, although the QTL on chromosome 2 does not match the chromosome arm location of our QTL. Similarly, several authors have reported a QTL on chromosome 10 for tuber shape (Van Eck et al, 1994 ; Prashar et al, 2014 ; Lindqvist-Kreuze et al, 2015 ), separating mainly compressed, round, and oval from the more elongated shape types oblong and long.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Bonierbale et al ( 1993 ) reported QTL on chromosomes 2, 4, and 7 for TTY, TS, and ATW, although the QTL on chromosome 2 does not match the chromosome arm location of our QTL. Similarly, several authors have reported a QTL on chromosome 10 for tuber shape (Van Eck et al, 1994 ; Prashar et al, 2014 ; Lindqvist-Kreuze et al, 2015 ), separating mainly compressed, round, and oval from the more elongated shape types oblong and long.…”
Section: Discussionmentioning
confidence: 74%
“…A cytokinin riboside 5′-monophosphate phosphoribohydrolase LOG3 gene is located in the QTL region at 56 Mb on chromosome 10. For tuber shape, several candidate genes associated with cell structure and function, and pectin metabolism have been reported in the major QTL located around 48 Mb on chromosome 10 (Lindqvist-Kreuze et al, 2015 ). Similarly, in the QTL region discovered in our analysis on chromosome 6, a Pectinesterase gene is located at 58 Mb.…”
Section: Discussionmentioning
confidence: 99%
“…Van Eck ( 2007 ) hypothesized on pleiotropic effect of one locus on both traits or two closely linked loci influencing eye depth and tuber shape. In studies of Lindqvist-Kreuze et al ( 2015 ), the QTL for eye depth and QTL for general tuber shape overlap on chromosome X with additional QTL for tuber shape found on chromosome V and QTL for eye depth on chromosome XII. Our results led to the conclusion that tuber shape and eye depth could not be explained by a simple one or two loci model as shown in studies mentioned above.…”
Section: Resultsmentioning
confidence: 96%
“…Initially, it was explained by a single locus Ro on chromosome 10, with round being dominant over long [ 27 ]. Other genetics studies identified several Quantitative Trait Loci (QTL) on different chromosomes affecting tuber shape [ 28 31 ]. Our previous study identified two QTL on chromosome 2 and 10 for tuber shape; the chromosome 10 QTL can explain the higher variation in the population as seen in other studies.…”
Section: Introductionmentioning
confidence: 99%